205.
1)
(x+1)³-(x-1)³=x(6x+2)=(x+1-x+1)((x+1)²+(x+1)(x-1)+(x-1)²)=6x²+2x
2(x²+2x+1+x²-1+x²-2x+1)=6x²+2x
2(3x²+1)=6x²+2x
6x²+2=6x²+2x
2x=2 I÷2
x=1.
2)
(x+2)³-(x-1)³=9x²+36
(x+2-x+1)((x+2)²+(x+2)(x-1)+(x-1)²)=9x²+36
3(x²+4x+4+x²+x-2+x²-2x+1)=9x²+36
3(3x²+3x+3)=9(x²+4)
9(x²+x+1)=9(x²+4) I÷9
x²+x+1=x²+4
x=3.
3)
(x-2)³-3x²-4=(x-3)³
(x-2)³-(x-3)³=3x²+4
(x-2-x+3)((x-2)²+(x-2)(x-3)+(x-3)²=3x²+4
1*(x²-4x+4+x²-5x+6+x²+6x+9)=3x²+4
3x²-3x+19=3x²+4
3x=15
x=5.
4)
(x+3)³=x²(x+9)
x³+9x²+27x+27=x³+9x²
27x=-27
x=-1.
206.
1)
(b+5)³-b(b-5)²-25(1+b)²=b³+15b²+75b+125-b³+10b²-25b-25b²-50b-25=100.
2)
5(1-b)³+5b(1+b)²-(1-5b)²=5-15b²+15b-5b³+5b+10b²+5b³-1+10b-25b²=?
3)
(2b-3)³-4b²(2b-6)+6b(2b-9)+10=8b³-36b²+54b-8b³+24b²+12b²-54b+10=10.
4)
(b+2)³+(2b+1)³-9b(b²+2b+2)=b³+6b²+12b+8+8b³+12b²+6b+1-9b³-18b²-18b=9.